(untitled) (Praxis Educativa, 2023)
Revising the didactics agenda from a reflexive, collective and situated perspective is a permanent task that constantly challenges those who teach general didactics. This article evaluates contributions and questions relating to the condition of possibility of an alternative teaching approach, situated within a context of cultural heterogeneity. Considering certain categories that arise from research into didactics, we propose that classical teaching concepts be reoriented in line with our complex reality, from a perspective that examines the inherited precepts of the modern science of Didactics. The concept of design is problematized and an intercultural teaching method outlined, called ñiminkaley. This category has arisen from the study of relationships between teaching methods and interculturality in southern Argentina, and this construction of didactic knowledge is closely linked to the main framework of critical affirmations in social sciences and the humanities.